Analysis of Language Errors in Social Media - Saptiana Sulastri; Desea Amanda Putri; Hillaria Stella Manora; Maria Mira Bella; Yesi Nursari (Raja Zulkarnain Education Foundation, 2026)
The development of social media such as Instagram, Facebook, and TikTok has influenced the way people communicate, especially in the use of Indonesian. This study aims to analyze the types of language errors that appear on social media, as well as the causes and impacts. The method used is descriptive qualitative, examining various examples of language use on social media. The results indicate that errors include spelling, morphology, syntax, and semantics. These errors are caused by the influence of slang, the speed of communication, a lack of understanding of language rules, and the influence of foreign languages. The impacts include a decline in the use of formal language and the potential for misunderstandings in communication. Increased awareness is needed to use Indonesian according to applicable rules. Furthermore, the way people speak on social platforms is often influenced by habits, convenience, and slang trends widely used by the public, especially the younger generation. This has resulted in a shift from formal to informal language. While the use of casual language can strengthen social relationships, excessive use without regard for rules can affect good and correct language skills, particularly in education. This phenomenon is a crucial issue because language is a national identity and also a primary means of communication in the world of education. If language errors are left unchecked, this can impact the quality of public literacy. Therefore, an in-depth study is needed regarding various types of language errors on social media so that it can become a basis for increasing awareness of the use of good and correct language.